2015
DOI: 10.1089/pho.2015.3907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Temperature Elevation During Root Canal Treatment with Dual Wavelength Laser: 2780 nm Er,Cr:YSGG and 940 nm Diode

Abstract: Objective: The purpose of this study was to observe the temperature elevation and evaluate the duration of its decreasing from root canal irrigant, as well as to observe smear layer removal ability of root canal surface when using of 940 nm diode laser as assistant in root canal sterilization. Background: laser irradiation may cause a thermal injury to the root structure and the surrounding periodontal tissues. Diode laser is weakly absorbed by water and tooth hard structure so it does not remove smear layer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
2
20
0
2
Order By: Relevance
“…The following settings were used during calibration and the experimental study: Er,Cr:YSGG-pulse duration 60 μs, repetition rate F I G U R E 1 Flow chart of study. Part 1: Calibrations of the double wavelength laser irradiation; Part 2: Experimental study using double wavelength laser irradiation 50 Hz (Al-Karadaghi et al, 2015;Gutknecht et al, 2016); 940 nm diode laser-continuous wave mode (CW). When water/air spray cooling was used, the device setting was 80% water-20% air.…”
Section: Laser Systemmentioning
confidence: 99%
“…The following settings were used during calibration and the experimental study: Er,Cr:YSGG-pulse duration 60 μs, repetition rate F I G U R E 1 Flow chart of study. Part 1: Calibrations of the double wavelength laser irradiation; Part 2: Experimental study using double wavelength laser irradiation 50 Hz (Al-Karadaghi et al, 2015;Gutknecht et al, 2016); 940 nm diode laser-continuous wave mode (CW). When water/air spray cooling was used, the device setting was 80% water-20% air.…”
Section: Laser Systemmentioning
confidence: 99%
“…In most studies, experimental groups showed better smear layer removal in coronal and middle third than in apical [10,17,18]. Additionally, Al-Karadaghi et al (2015) [19] observed that Er, Cr: YSGG laser had an uneven smear layer removal especially in the apical third of the root canal wall. This is attributed to many reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Laser irradiation was performed in continuous mode (CW), power of 0.540 W (AE 0.019 W) and irradiation time for 5 s. Power density was 1718.9 W/cm 2 at laser tip, and total irradiation dose was 8594.3 J/cm 2 . The power was selected at 0.5 W to avoid possible thermal alterations in dentin and to comply with the effect of a power range used for 940 nm diode laser-assisted root canal disinfection and transmission studies (20,21).…”
Section: Laser Systemmentioning
confidence: 99%